Evaluating ionic conductivity in DMSO − NaCF3SO3 electrolytes: the role of charge carrier concentration and mobility - Shamshurim, N.; Tamchek, N.; Singh, Pramod K.; Noor, I. M. (Springer Science and Business Media Deutschland, 2025)
Understanding the factors that influence conductivity changes in electrolyte systems due to salt doping is important for optimizing their performance. This work quantitatively evaluated key transport parameters, namely diffusivity (D), mobility (µ), and concentration (n) of charge carriers, and the Stokes drag coefficient (Fd) using the Nyquist plot fitting method. A liquid electrolyte system with varying concentrations of sodium trifluoromethanesulfonate (NaCF3SO3) in dimethyl sulfoxide (DMSO) was prepared. The conductivity increased from 1.00 × 10−2 S cm−1 (L1 electrolyte containing 0.6 M NaCF3SO3) to 1.14 × 10−2 S cm−1 (L3 electrolyte containing 1.0 M NaCF3SO3), driven by an increase in n from 6.70 × 1020 cm−3 (L1 electrolyte) to 7.43 × 1020 cm−3 (L3 electrolyte), indicating increased ion dissociation within the electrolyte. The conductivity decreased to 1.03 × 10−2 cm−3 (L4 electrolyte containing 1.2 M NaCF3SO3) due to decrease in both µ and D, from 9.54 × 10−5 to 6.94 × 10−6 cm2 V−1 s−2 and from 2.47 × 10 to 1.79 × 10−6 cm2 s−1, respectively, due to the higher availability of free ions in the electrolyte. The Fd values also increased, indicating increased viscosity and reduced ion movement. These findings suggest that the conductivity variations for DMSO − NaCF3SO3 liquid electrolytes are primarily influenced by µ, D, and Fd, rather than n.